TRADISI ZIKIR BERDIRI DALAM RITUAL DO’A MINTA HUJAN PADA MASYARAKAT PANIPAHAN (Studi Living Qur’an di Kelurahan Panipahan Kecamatan Pasir Limau Kapas Kabupaten Rokan Hilir) - Yus, M. Haris; Nawawi, Abd Muid; Nurbaiti, Nurbaiti (Statement: Jurnal Media Informasi Sosial dan Pendidikan, 2023)
This study aims to discuss the tradition of standing remembrance in the ritual of praying for rain during a long dry season in the Panipahan community (Study of Living Qur'an in Panipahan Village, Pasir Limau Kapas District, Rokan Hilir Regency). This study uses a qualitative method with a sociological phenomenological approach. Primary data sources come from important documents owned by community institutions, as well as answers from related parties interviewed. While secondary sources come from various scientific references related to the discussion. There is a debate among Muslim scholars about the study of the living Qur'an, namely groups that support and groups that criticize the study of the living Qur'an. The groups that support the living Qur'an are Jalaluddin as-Suyuthi and Badruddin az-Zarkasyi. Meanwhile, groups that criticize the living Qur'an are Fazlur Rahman, Nasr Hamid Abu Zaid, and Farid Esack. In addition, one of the Indonesian figures who also criticized the Qur'an was Mun'im Sirry. The findings of this study indicate that the social and Qur'anic meaning of the tradition of remembrance stands in the ritual of praying for rain during a long dry season in the Panipahan community. This is evidenced by the reading of the sentence remembrance la ilâha illallah, we are remembrance of Allah asking Allah to help bring down rain in our village by standing and rotating clockwise. Where from the reading of the remembrance the people believe and believe that Allah SWT, will be pleased with everything they do and Allah SWT, will always pour out His mercy and protect and protect them and grant what they ask for when the ritual of remembrance stands asking for rain to fall because has been dry due to drought that never stops